A practical approach to detection and treatment of depression in Parkinson disease and dementia. Issue 2 (April 2017) - Goodarzi, Zahra; Ismail, Zahinoor
Abstract: Purpose of review: To review the available evidence for the detection and management of depression in Parkinson disease (PD) and dementia. Recent findings: Depression is a common comorbidity in those with PD or dementia, and leads to increased morbidity. There are several available and accurate tools for the detection of depression in PD (e.g., Geriatric Depression Scale) and dementia (e.g., Cornell Scale for Depression in Dementia). Treatment of depression depends on patient preference, severity of depression, comorbidities, and available resources. Despite variable evidence, the use of nonpharmacologic strategies to manage depression is suggested. Pharmacologic management is guided by modest evidence in PD and dementia, but also informed by the management of late-life depression (LLD). Summary: There is evidence to guide the diagnosis and management of depression in PD or dementia. However, more research is required in this field to better inform clinical decision-making.